Tarefas duplas no futebol: efeitos do treinamento em pequenos jogos no processo de tomada de decisão e na memória de trabalho de jovens jogadores - Pedro Emílio Drumond Moreira (2023)
Dual tasks (DT) are characterized by the performance of two simultaneous tasks, used to measure an individual's cognitive and motor capacity. Engaging in DT represents an efficient training condition for enhancing cognitive processes in individuals with mental illnesses and in the elderly population. In the context of sports, despite the limited number of investigations, previous studies have also identified benefits of training with DT in a laboratory setting for the decision-making process. However, little is known about the impacts of this training in an environment with greater ecological validity. The current thesis had three aims: a) to investigate through a systematic review the acute and chronic effects of DT on the cognitive and motor performances of athletes; b) to compare the tactical performance of soccer players in small-sided games with and without DT; c) to assess the effects of a training program that incorporates DT demands in small-sided games on working memory capacity and tactical performance of soccer players. For the first objective, regarding the acute effects, the review showed a decline in decision-making performance, working memory, and attentional processes in athletes, with improvement in these aspects following DT training – the chronic effect. Regarding the second objective, 24 under-13 soccer players participated in four different small-sided games: single task (ST) - playing small-sided games only; dual motor task (DMT) – small-sided games while balancing a basketball on a mini cone; dual cognitive task 1 (DCT1) – small-sided games and mathematical operations; dual cognitive task 2 (DCT2) – small-sided games and a memorization task. Players exhibited better tactical performance in ST compared to all experimental DT conditions. It was concluded that there is a decrease in tactical performance in small-sided game situations with DT. Concerning the third objective, 40 under-14 soccer players from two clubs were selected and assigned to three groups: experimental group (EG), which participated in 14 sessions of small-sided games with DT; active control group (ACG), which participated in 14 sessions of small-sided games without DT; and passive control group (PCG), which did not participate in the study's training. The focus was on the principle of width and length as the training content. In the DT training, two memorization tasks and a basketball balancing task were selected as secondary tasks. Tactical performance was evaluated using the Tactical Assessment System in Soccer, and working memory was assessed using the Digit Span test. The results indicated that the EG demonstrated improved tactical performance in off-the-ball width and length principle compared to the PCG in post-training [F (2,35) = 4,0; p= 0,02; η²p= 0,19 – small size] and retention moments [F (2,35) = 3,5; p= 0,04; η²p= 0,17 – small size], and the EG and ACG showed superior offensive tactical performance compared to the ACG during the retention moment [F (2,35) = 6,1; p= 0,005; η²p= 0,26 – moderate effect]. Additionally, no differences were observed among the groups in working memory performance. It is concluded that training with DT in small-sided games enhances the tactical performance of young soccer players, but there is no observed improvement in overall working memory capacity.